Early experience with a patient‐specific virtual surgical simulation for rehearsal of endoscopic skull‐base surgery. Issue 1 (3rd November 2017) - Won, Tae‐Bin; Hwang, Peter; Lim, Jae Hyun; Cho, Sung‐Woo; Paek, Sun Ha; Losorelli, Steven; Vaisbuch, Yona; Chan, Sonny; Salisbury, Kenneth; Blevins, Nikolas H.
Abstract : Background: With the help of contemporary computer technology it is possible to create a virtual surgical environment (VSE) for training. This article describes a patient‐specific virtual rhinologic surgical simulation platform that supports rehearsal of endoscopic skull‐base surgery. We also share our early experience with select cases. Methods: A rhinologic VSE was developed, featuring a highly efficient direct 3‐dimensional (3D) volume renderer with simultaneous stereoscopic feedback during surgical manipulation of the virtual anatomy, as well as high‐fidelity haptic feedback. We conducted a retrospective analysis on 10 patients who underwent various forms of sinus and ventral skull‐base surgery to assess the ability of the rhinologic VSE to replicate actual intraoperative findings. Results: In all 10 cases, the simulation experience was realistic enough to perform dissections in a similar manner as in the actual surgery. Excellent correlation was found in terms of surgical exposure, anatomical features, and the locations of pathology. Conclusion: The current rhinologic VSE shows sufficient realism to allow patient‐specific surgical rehearsal of the sinus and ventral skull base. Further validation studies are needed to assess the benefits of performing patient‐specific rehearsal.